Healing the child within : discovery and recovery for adult children of dysfunctional families - Whitfield, Charles L. (Health Communications, 1987)
Describes how the inner child is denied as a result of early trauma and loss, and how by recovering it we can heal the fear, confusion, and unhappiness of adult life.